Optimal degree of smart transformer substations in distribution networks for reliability improvement - Rodríguez Calvo, Andrea; Frías Marín, Pablo; Reneses Guillén, Javier; Mateo Domingo, Carlos (Sin editorial (Berlín, Alemania), 2013)
The medium to low voltage transformer substation is a key element in the distribution system. Therefore, smart transformer substations will play a crucial role in the evolution of distribution towards the smart grid. Smart transformer substations can provide a significant improvement of continuity of supply. However, a large investment is required, so the optimal degree of automation must be determined. The main objective of this paper is to quantify the impact of smart MVLV transformer substations on continuity of supply, which is essential to determine the optimal automation degree. The analysis has considered different degrees of implementation of smart MVLV substations for different configuration schemes of urban distribution networks. Furthermore, sensitivity analyses have been performed for the main parameters involved so that conclusions on reliability improvement achieved by MVLV transformer substation automation can be scaled up.

The medium to low voltage transformer substation is a key element in the distribution system. Therefore, smart transformer substations will play a crucial role in the evolution of distribution towards the smart grid. Smart transformer substations can provide a significant improvement of continuity of supply. However, a large investment is required, so the optimal degree of automation must be determined. The main objective of this paper is to quantify the impact of smart MVLV transformer substations on continuity of supply, which is essential to determine the optimal automation degree. The analysis has considered different degrees of implementation of smart MVLV substations for different configuration schemes of urban distribution networks. Furthermore, sensitivity analyses have been performed for the main parameters involved so that conclusions on reliability improvement achieved by MVLV transformer substation automation can be scaled up.
Capítulos en libros
Keywords: Instituto de Investigación Tecnológica (IIT)